Formation of Learning Motivation in Islamic Religious Education Through Ceramah Plus Method and Spiritual Activities - Ahmad Ihwanul Muttaqin; Zahrotul Wardah; Imam Syafi’i (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
This article is based on academic concerns mentioning that the motivation for learning Islamic Education is low. It is supported by the findings of field research conducted by numerous researchers stating that Indonesia's Human Development Index remains low, especially when observed through the results of the Programme for International Student Assessment (PISA) released by the Organisation for Economic Co-operation and Development (OECD) in 2018. According to the release, Indonesia's scores declined in all categories, with reading scores going from 397 to 371, mathematics from 386 to 379, and science from 403 to 396. One of the reasons for this decline is the students' low learning motivation due to the lack of diverse teaching methods. This article is the result of field research using a qualitative approach that was carried out at Miftahul Ulum Klakah Lumajang Junior High School. Field research focuses on the implementation of the lecture plus method and the addition of spiritual activities in the learning process. The results of the study stated that an increase in learning motivation could occur by providing a variety of plus models in lectures and other spiritual activities such as reading al-Asma al-Husna, giving ibrah and uswah from leaders and sharing experiences.